PENERAPAN SPONGE CITY PADA KAWASAN KAMPUNG MANGGARAI, JAKARTA - Larasati, Finky; Tanjung, Fadly; Haq, Harun; Afif, Irfan (LPPM Universitas Terbuka, 2023)
The density of urban areas due to population growth causes the emergence of slum settlements. This condition is often found in settlements located on the river border of DKI Jakarta Province, especially Manggarai Village. The existence of this residential land has an impact on changing the proportion of land cover, thereby reducing the water catchment area. This study applies the sponge city concept which has been adapted to the needs of the study area. Methods of collecting data were interviews, observations, and secondary data acquisition. The method of analysis is carried out by comparing the criteria for the three elements of the plan, namely (a) Green Neighborhood (b) Permeable Road (c) Utility to existing conditions using the gap analysis method to produce recommendations. This study was conducted by designing a slum area to solve the flood problem. Some recommendations that can be made include: (1) Adding water catchment areas; (2) Structuring the built-up area by providing vertical residential buildings; (3) Application of road construction with environmentally friendly materials and high water absorption capacity, such as permeable paving blocks; (4) Provision of rainwater runoff management facilities such as infiltration wells, bioswales, and retention ponds.